(untitled) (Research, Society and Development, 2023)
Electronic cigarettes (EC) are devices that use the heating of a liquid with toxic chemical substances and flavorings, with different types, brands, shapes and sizes, making them more attractive. The largest audience is teenagers and young adults, whether they are smokers or not. Despite not having the burning and smoke production, with the substances generated by conventional cigarettes (CC), they are not exempt from negative effects. This study aims to talk about the health risks related to the use of electronic cigarettes. Searches were carried out in the MEDLINE, LILACS AND BDENF, with 18 articles being found and after analysis, 8 articles were selected for final sampling. Due to the consequences, Brazil was one of the pioneers in banning the use of EC, which is sold as a substitute for CC, although said "less harmful" are not exempt from affecting health. But its popularity has increased more and more, with the consuming public, going through all the inspection and regulation. In addition, it leaves them confused about the product because it has several components and a lot of encouragement to use it. It was evident that despite the data and advertisements suggesting less toxicity in relation to conventional cigarettes, it does not there are studies that confirm its positive effect as an alternative use, in addition to the emissions of cytotoxic and carcinogenic substances and the need for political and regulatory decisions on the use of ECs.